Human Essence and Spiritual Need: A Comparative Analysis of Religious Doctrine and Human Nature - Afiralda, Iffa; Hasibuan, Renni (Al-Maktabah: Jurnal Studi Islam Interdisiplin, 2024)
The exploration of human essence and the intrinsic spiritual need has become increasingly crucial in understanding how religious doctrines shape and reflect the fundamental nature of humanity, highlighting the ongoing interplay between belief systems and human identity across different cultures and philosophies. This research utilizes library research methods by analyzing primary data such as research books and theses, and secondary data including relevant books, articles, and journals. The data is analyzed using both deductive and inductive approaches.  The result research shows that humans, with all their unique capacities and abilities, have a fundamental need for religion and religious doctrine. From the perspective of religion and philosophy, humans are recognized as multifaceted beings capable of rational thought, speech, cooperation in society, and the pursuit of spiritual meaning. Religion provides moral, psychological, and social guidance that helps humans achieve physical and mental well-being in this life and the next. These findings imply that a deep understanding of human essence and spiritual needs, through religious doctrine, can provide valuable guidance for the development of educational policies and social interventions that support human physical and mental well-being in a religious and philosophical context.